2021
DOI: 10.3892/etm.2021.9916
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 ORF3a induces the expression of ACE2 in oral and pulmonary epithelial cells and the food supplement Vita Deyun® diminishes this effect

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become a serious global health problem and numerous studies are currently being conducted to improve understanding of the components of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, as well as to identify solutions that mitigate the effects of COVID-19 symptoms. The nutritional supplement Vita Deyun ® is composed of silymarin, glutathione, vitamin C and selenium. Studies of its individual components have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…It can be summarized that silymarin extracted from milk thistle, has a protective effect during lung injury because of its ability to decrease the production of nitric oxide, decrease the infiltration of inflammatory cells, suppress the activity of myeloperoxidase and its ability to reduce the protein levels of pro-inflammatory mediators, superoxide dismutase, catalase and GSH peroxidase [50] . Additionally, silymarin has been considered recently as a potent inhibitor for angiotensin converting enzyme-2 preventing its host-cell entry [51] .…”
Section: Discussionmentioning
confidence: 99%
“…It can be summarized that silymarin extracted from milk thistle, has a protective effect during lung injury because of its ability to decrease the production of nitric oxide, decrease the infiltration of inflammatory cells, suppress the activity of myeloperoxidase and its ability to reduce the protein levels of pro-inflammatory mediators, superoxide dismutase, catalase and GSH peroxidase [50] . Additionally, silymarin has been considered recently as a potent inhibitor for angiotensin converting enzyme-2 preventing its host-cell entry [51] .…”
Section: Discussionmentioning
confidence: 99%
“…The HE acts as a receptor-destroying enzyme in the binding of SARS-CoV-2 to the ACE receptors. Besides, studies indicated that silymarin might inhibit the host-cell entrance of SARS-Cov-2 by inhibiting ACE-2 receptors [30] . Zhang et al [111] suggested that a timely anti-inflammation therapy, including glucocorticoids, JAK inhibitors, and IL-6 antagonists, in COVID-19 patients may have the most beneficial effects.…”
Section: Resultsmentioning
confidence: 99%
“…Silibinin can affect viral RNA-dependent RNA polymerase action, preventing hepatitis C virus replication [29] . Silibinin has been reported for its anti-inflammatory and anti-oxidative activity and protective effects against endothelial dysfunction in both in vitro [30] and in vivo [22] studies. Nieuwenhuizen et al concluded that silymarin has a protective effect against lung injury due to its ability to decrease the production of nitric oxide, the infiltration of inflammatory cells, the activity of myeloperoxidase, and its ability to decrease the protein levels of pro-inflammatory mediators, catalase, superoxide dismutase, and GSH peroxidase [31] .…”
Section: Introductionmentioning
confidence: 99%
“…61 Additionally, silymarin has recently been considered a potent inhibitor for ACE2, preventing its host-cell entry. 62 Nemany et al recently found silymarin/curcumin-loaded albumin nanoparticles coated with chitosan and used in a muco-inhalable delivery system had anti-inflammatory and anti-COVID-19 effects. 63,64 Studies on viral infections have shown overactive inflammasome and therefore, destructive and systemic inflammation in patients.…”
Section: Effect Of Curcumin On Treating Covid-19mentioning
confidence: 99%
“…Silymarin, extracted from milk thistle, has a protective effect during lung injury because of its ability to decrease the production of nitric oxide and the infiltration of inflammatory cells 61 . Additionally, silymarin has recently been considered a potent inhibitor for ACE2, preventing its host‐cell entry 62 . Nemany et al recently found silymarin/curcumin‐loaded albumin nanoparticles coated with chitosan and used in a muco‐inhalable delivery system had anti‐inflammatory and anti‐COVID‐19 effects 63,64 …”
Section: Effect Of Curcumin On Treating Covid‐19mentioning
confidence: 99%